Oral Zinc Sulfate for Prevention and Treatment of Chemotherapy-Induced Oral Mucositis: A Meta-Analysis of Five Randomized Controlled Trials - Tian, Xu; Liu, Xiao-Ling; Pi, Yuan-Ping; Chen, Hui; Chen, Wei-Qing (Frontiers in Oncology, 2018)
Chemotherapy-induced oral mucositis is an extremely serious complication faced by cancer patients. The role of oral zinc sulfate in preventing and treating chemotherapy-induced oral mucositis remains a subject of debate. The aim of this systematic review is to assess the potential of oral zinc sulfate to alleviate this morbid condition. A systematic search was conducted electronically in PubMed, EMBASE, and the Cochrane Central Register of Controlled Trials (CENTRAL) to capture all potential randomized controlled trials investigating efficacy and safety of oral zinc sulfate in prevention and treatment of chemotherapy-induced oral mucositis, and the retrieval time was limited from their inception to April 2018. We assigned two independent investigators to perform a search, screen citations, extract information, and evaluate the risk of bias in all included trials. Subsequently, the RevMan 5.3 software was utilized to perform all statistical analyses. We included five eligible studies involving 352 patients. Meta-analysis based on limited data revealed that oral zinc sulfate failed to decrease the incidence of chemotherapy-induced oral mucositis (RR [relative risk] = 0.52, 95% CI [confidence interval] = 0.17–1.64) as well as relieve chemotherapy-induced oral mucositits grade (RR = 0.62, 95% CI = 0.11–3.56; RR = 0.70, 95% CI = 0.29–1.71). Moreover, qualitative analyses also suggested that oral zinc sulfate was not associated with reduced oral pain intensity, delayed onset of chemotherapy-induced oral mucositis, decreased adverse events, or improved quality of life compared with control regimes. Oral zinc sulfate may not provide clinical benefits in preventing or reducing incidence, severity, or pain intensity of chemotherapy-induced oral mucositis in cancer patients. However, more studies with large-scale and rigorous methods are warranted for the purpose of further investigating efficacy and safety of oral zinc sulfate for this pathologic condition due to the presence of limitations.